E-Tailing : A Virtual Channel For Shopping - J. Rajan and Ambili G.S (REVIEW OF SOCIAL SCIENCES, 2013)
The retail market is witnessing a new way of shopping, i.e., Internet Retailing. It is the most innovative and challenging contribution to the retail industry. A large number of consumers are frequently using internet for shopping. This includes a wide range of scenarios such as shopping, entertainment, knowledge- transfer and business exchanges. E-tailing involves retailing by using a variety of technologies. With a few click, the customer can order the products according to their choice. The product will reach to the customer within a few days. E-tailing helps the customers by offers additional channel of information, variety choice for purchase, cost savings and convenience. E-tailing is a convenient shopping method not only to the online buyers but also it helps the retailers in terms of lower distribution costs, less inventory and less human capital. It has become imperative for e-tailers to understand in great depth the purchase behavior of online customer’s in order to design and support effective websites that match the preferences of their target markets. Internet retailing had witnessed a remarkable growth in the global scenario by gaining a significant share in overall retail sales. E-tailing in India is in growth stage. In India, online business has certainly exhibited an upward thrust with powerful organized retailers venturing in to e-business arena. This study is mainly focused on the growth and importance of e-tailing in Indian economy.